Asymptotic Behavior of the Solutions of System of Difference Equations of Exponential Form. (13th October 2014) - Van Khuong, Vu; Hong Thai, Tran
Abstract : The goal of this paper is to study the boundedness, the persistence, and the asymptotic behavior of the positive solutions of the system of two difference equations of exponential form:x n + 1 = a + b e - y n + c e - x n / d + h y n, y n + 1 = a + b e - x n + c e - y n / d + h x n, wherea, b, c, d, andh are positive constants and the initial valuesx 0, y 0 are positive real values. Also, we determine the rate of convergence of a solution that converges to the equilibriumE = ( x -, y - ) of this system.